Comparative Histoenzymic Distribution of Phosphatases and Oxidoreductases in Skin of Domestic Animals - Raghav, Shweta (Indian Journal of Veterinary Anatomy, 2020)
The present study was conducted on skin of adult cattle, buffalo, dog, pig, goat and horse (six sample of each), collected from the abattoir and postmortem hall. The study revealed that there were no comparable differences observed in activity of alkaline phosphatase (AKPase), glucose-6-phosphatase (G-6-Pase), succinate dehydrogenase (SDH), lactate dehydrogenase (LDH), glucose-6-phosphate dehydrogenase (G-6-PD), alcoholic dehydrogenase (ALC), glutamic dehydrogenase (GLD), malic dehydrogenase (MDH), reduced nicotinamide adenine dinucleotide diaphorase (NADH-diaphorase), reduced nicotinamide adenine dinucleotide phosphate diaphorase (NADPH diaphorase) and non-specific esterase (NSE). However the SDH activity was slightly less in stratum basale of horse and pig whereas LDH activity was more in stratum basale and stratum spinosum in horse. NADH activity was more in stratum basale and stratum spinosum of dog and horse and G-6PD activity was less in horse.